The Album “Guernica” by the “KAT” band: a Musical Representation of a Painting by Pablo Picasso - Palkina, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. Rock art has a syncretic origin and gravitates towards multi-level synthesis throughout the history of its development. Incorporating elements from other art forms is an essential characteristic of rock music. The trends in the interaction of art forms in the field of rock culture are considered on the example of the concept album “Guernica” by the “KAT” band, dedicated to the cognominal painting by Pablo Picasso. The main source of analysis is the audio recording of the album. The “Guernica” album is a vivid example of an artistic dialogue that takes place on the literary, musical and visual planes. The scientific novelty of the study. The concept album “Guernica” by the Ukrainian hardcore band “KAT”, dedicated to the painting of the same name by Pablo Picasso, for the first time became the object of musicological analysis and is considered as an example of synthesizing trends in the field of rock art. The main objective of the study is to determine the levels of artistic interactions between the concept album “Guernica” by the “KAT” band and the original painting by Pablo Picasso. The methodology is based on the contextual method (to consider rock art as a synthetic phenomenon) as well as methods of holistic (to describe the album), comparative and intermedial analysis (to identify the levels of artistic interaction between a piece of music and the original painting). Results of the study. The concept album “Guernica” by the hardcore band named “KAT” is not just a dedication to the cognominal painting by Pablo Picasso. Аrtistic dialogue between works of art takes place in the visual (album cover), literary (direct descriptions of the elements of the picture, the technique of seeing events from different angles borrowed from visual art, reportage style of texts) and musical plane (recitative intonations, fast drumbeats, extreme vocal techniques); on the descriptive (direct references to the elements of the picture) and emotional and figurative levels. The album is a vivid example of intermediality in the field of rock art.